2020
DOI: 10.21203/rs.2.22904/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated total homocysteine predicts in-hospital pneumonia and poor functional outcomes in acute ischemic stroke

Abstract: Background The impact of elevated total homocysteine (tHcy) on functional outcomes and pneumonia after acute ischemic stroke (AIS) is still not well understood. We investigated the association between tHcy levels upon hospital admission and in-hospital short-term outcomes in AIS patients. Methods A total of 2,084 AIS patients enrolled from December 2013 to May 2014 across 22 hospitals in Suzhou city were included in the present study. We divided patients into 4 groups according to their level of admission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…Elevated Hcy was a marker of spontaneous bacterial peritonitis in patients with cirrhotic ascites (15). You et al found that a higher level of homocysteine at admission was independently associated with in-hospital pneumonia, in-hospital mortality, and poor functional outcome in the hospital (10). Likewise, we demonstrated that Hcy was independently associated with HAP in ICH.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Elevated Hcy was a marker of spontaneous bacterial peritonitis in patients with cirrhotic ascites (15). You et al found that a higher level of homocysteine at admission was independently associated with in-hospital pneumonia, in-hospital mortality, and poor functional outcome in the hospital (10). Likewise, we demonstrated that Hcy was independently associated with HAP in ICH.…”
Section: Discussionsupporting
confidence: 77%
“…Over the last decade, a strong association between Hcy and induction of inflammatory determinants in both human and experimental models has been demonstrated (6)(7)(8)(9). A previous study has proved that a high admission Hcy level is independently associated with HAP in patients with acute ischemic stroke (10). Based on this, we proposed the hypothesis that Hcy was an independent predictor for HAP in primary ICH.…”
Section: Introductionmentioning
confidence: 82%